Personality and Cognition in Gamers: Avoidance Expectancies Mediate the Relationship Between Maladaptive Personality Traits and Symptoms of Internet-Gaming Disorder - Laier, Christian; Wegmann, Elisa; Brand, Matthias (Frontiers in Psychiatry, 2018)
Internet-gaming disorder (IGD) has become a clinically relevant phenomenon worth investigating with respect to its mechanisms of development and maintenance. Considering theoretical models of specific Internet-use disorders, we assumed an interaction of maladaptive personality traits as unspecific predisposing factors and experience-based, gaming-related Internet-use expectancies in predicting symptoms of IGD. Therefore, 103 male and female regular Internet gamers were investigated with questionnaires assessing maladaptive personality traits in accordance to DSM-5, gaming-related positive and avoidance Internet-use expectancies, and symptoms of IGD. The results demonstrated that negative affectivity, detachment, antagonism, disinhibition, psychoticism as well as gaming-related positive and avoidance expectancies were related to symptoms of IGD. Moreover, the relationship between maladaptive personality traits as represented by negative affectivity, detachment, and psychoticism with symptoms of IGD was mediated by avoidance expectancies. Positive gaming-related use expectancies were related to detachment, and were not a significant mediator in the hypothesized model. The findings give reason to assume that maladaptive personality traits in combination with gaming-related positive expectancies and avoidance expectancies are important factors for the development of IGD, but that positive expectancies and avoidance expectancies play a differential role regarding there mediating role between personality characteristics and symptoms of IGD.